Novel gold nanoparticles reduced by Sargassum glaucescens: preparation, characterization and anticancer activity - Ajdari, Zahra; Rahman, Heshu; Shameli, Kamyar; Abdullah, Rasedee; Abd Ghani, Maaruf; Yeap, Swee; Abbasiliasi, Sahar; Ajdari, Daniel; Ariff, Arbakariya (MDPI, 2016)
The current study investigated the anticancer properties of gold nanoparticles (SG-stabilized AuNPs) synthesized using water extracts of the brown seaweed Sargassum glaucescens (SG). SG-stabilized AuNPs were characterized by ultraviolet-visible spectroscopy, transmission and scanning electron microscopy, and energy dispersive X-ray fluorescence spectrometry. The SG-stabilized AuNPs were stable and small at 3.65 ± 1.69 nm in size. The in vitro anticancer effect of SG-stabilized AuNPs was determined on cervical (HeLa), liver (HepG2), breast (MDA-MB-231) and leukemia (CEM-ss) cell lines using fluorescence microscopy, flow cytometry, caspase activity determination, and MTT assays. After 72 h treatment, SG-stabilized AuNPs was shown to be significant (p < 0.05) cytotoxic to the cancer cells in a dose- and time-dependent manner. The IC50 values of SG-stabilized AuNPs on the HeLa, HepG2, CEM-ss, MDA-MB-231 cell lines were 4.75 ± 1.23, 7.14 ± 1.45, 10.32 ± 1.5, and 11.82 ± 0.9 μg/mL, respectively. On the other hand, SG-stabilized AuNPs showed no cytotoxic effect towards the normal human mammary epithelial cells (MCF-10A). SG-stabilized AuNPs significantly (p < 0.05) arrest HeLa cell cycle at G2/M phase and significantly (p < 0.05) activated caspases-3 and -9 activities. The anticancer effect of SG-stabilized AuNPs is via the intrinsic apoptotic pathway. The study showed that SG-stabilized AuNPs is a good candidate to be developed into a chemotherapeutic compound for the treatment of cancers especially cervical cancer.